Investigation Mechanism to Obtain Information from Suspects Allegedly Committing Criminal Acts: Mekanisme Penyidikan untuk Mendapatkan Keterangan Terhadap Tersangka yang Diduga Melakukan Tindak Pidana - Romlih, Rheihan Nurrizki; Prasetyo, Boedi (Indonesian Journal of Law and Economics Review, 2026)
General background of this study lies in the central role of investigation as a crucial stage in the Indonesian criminal justice process, where investigators are responsible for collecting evidence and obtaining suspect statements under KUHAP. Specific background concerns recurring procedural deviations in practice, including coercive interrogation, absence of legal counsel, and improper documentation, which undermine due process and violate constitutional protections. Knowledge gap emerges from limited scholarly analysis that systematically connects the normative framework of KUHAP with its practical implementation in suspect examinations. This study aims to examine the investigation mechanisms for obtaining suspect statements while prioritizing legal protection, based on a normative legal research method analyzing statutory rules and legal doctrine. Results show that although KUHAP clearly regulates summons procedures, notification of rights, voluntary statements, prohibition of coercion, and standardized documentation through BAP, significant discrepancies remain in field practices. Novelty of this research lies in offering an integrated assessment of normative provisions, operational challenges, and concrete procedural reforms, particularly mandatory audio-visual recording and strengthened oversight. Implications highlight the urgency of improving investigator professionalism and ensuring transparent, accountable investigations to safeguard suspect rights and preserve the integrity of the criminal justice system. Highlights: Clear KUHAP procedures often differ from actual investigative practices. Suspect statements must be obtained voluntarily without coercion. Strong oversight and audio-visual recording are essential for accountable investigations. Keywords: Investigation, Suspect Rights, KUHAP, Legal Protection, Criminal Procedure